Faktor mempengaruhi kemalangan di tempat kerja dalam kalangan anggota kesihatan di bawah penyeliaan Unit Penolong Pegawai Perubatan, Hospital Daerah Kluang - Idzuani Elmi, Kamilan (2020)
The study aimed to examine the factors of accidents (work stress, unsafe behavior, equipment, unsafe work, and training) that occurred among health workers consisting of 237 Assistant Medical Officers, Health Care Assistants, and Guides. This study used quantitative design where out of 237 distributed only 222 research questions were accepted. This study was analyzed using the Statistical Package for Social Science (SPSS) Version 5 where correlation and regression analyzes were used. The results showed that of the 5 independent variables only 4 independent variables had significant positive correlation to workplace accidents namely job stress, insecurity, equipment, and training. Only unsafe workplace variables have no positive correlation with workplace accidents. Multiple regression analyzes showed that 3 out of 5 factors had positive effect on workplace accidents. This includes job stress, unsafe behavior and training. Two variables, namely equipment and unsafe workplace, have negative effect on workplace accidents. This means that the better the equipment used and the more safety training provided directly it will reduce accidents at work. The whole factor of workplace accidents requires a more detailed and comprehensive study because of the impact they put on employers, workers and the country especially on labor, money and infrastructure.